Pengaruh Kompetensi terhadap Kinerja Pegawai dengan Komitmen Organisasi sebagai Variabel Intervening di Kantor Kecamatan Kota Pekanbaru - Rein Rizka Karvy; Sujianto Sujianto; Meyzi Heriyanto; Adianto Adianto (Nakhoda: Jurnal Ilmu Pemerintahan, 2026)
This study examines the effect of competence on employee performance and investigates the mediating role of organizational commitment among employees of subdistrict offices in Pekanbaru City. A quantitative approach using partial least squares structural equation modeling was employed, based on data collected from 151 employees across five subdistrict offices through purposive sampling. The findings indicate that competence has a significant positive effect on organizational commitment (? = 0.954, p < .001) and employee performance (? = 0.758, p < .05). Organizational commitment also has a significant positive effect on employee performance (? = 0.236, p < .05) and partially mediates the relationship between competence and employee performance (indirect effect = 0.225). These results suggest that competence enhances employee performance both directly and indirectly through organizational commitment. This study contributes to the literature on public sector human resource management by providing empirical evidence that organizational commitment serves as a partial mediator between competence and employee performance. The findings offer practical insights for improving employee performance within local government institutions, particularly at the subdistrict level in Pekanbaru City.